Respostas

2014-05-27T20:05:07-03:00
P/ a = 1/x // b = 1/y
(1) 1/x + 1/y = 3/2 => a + b = 3/2 => a = (3/2 - b)
(2) 1/ x² + 1/y² = 5/4 => a² + b² = 5/4, substituindo (1) em (2):
(3/2 - b)² + b² = 5/4 => (9/4 - 2.3/2.b + b²) - b² = 5/4 => 9/4 - 3b + b² - b² = 5/4 =>
=> 9/4 - 3b = 5/4 => -3b = 5/4 - 9/4 => -3b =  - 4/4 (-1) => 3b = 1 => b = 1/3, substituindo em (1):
a = 3/2 - 1/3 => a = (9 - 2)/6 => a = 7/6
a = 1/x => x = 1/a => x = 6/7
b = 1/y => y = 1/b => y = 3
O conjunto solução do sistema é (6/7, 3)
1 5 1